Obtenção e caracterização de pulmão e coração suíno desidratados por diferentes processos de secagem - Freitas, Mariana Pinto (2024)
In the industrial sector, the generation of waste is common, in the meat sector. In cold storage slaughterhouses there are daily meat processing operations, which generate a significant amount of by-products. Among the alternatives for using this material we have the use of by-products for animal feed. In the case of pig slaughter, their viscera such as the lungs and heart can provide a source of protein and vitamins for the production of petfood. Drying is a method used by the industry to preserve by-products in the form of flour. This work evaluated the drying methods (air fryer, convective oven and freeze-drying), and their respective temperature conditions of 80, 90 and 160 ºC and a thickness of 2 mm, to produce and characterize the porcine lung and heart. The proximate composition of the viscera in natura was determined, as well as their physical properties after the drying processes. The results concluded that porcine lungs and hearts are by-products with nutritional potential, as they contain 11.91% and 20.29% of protein, respectively. Therefore, in the drying kinetic curves for the lung in an air oven at temperatures of 80 and 90 ºC, a temporal evolution of humidity was observed with drying at times of 140 and 160 min to obtain humidity levels below 0.30 g water/g dry solids. For a temperature of 160 ºC, this same humidity value was reached with an average time of 65 min. Therefore, the heart, under the same conditions and at temperatures of 80 and 90 ºC, showed similar behavior. Lower humidity levels were obtained from 110, 100 and 50 min for temperatures of 80, 90 and 160 ºC. Through air fryer drying kinetics, it was observed that humidity levels below 23% were reached after 130 and 40 min, for temperatures of 90 and 160 ºC. Therefore, the initial humidity of the heart is lower than that of the porcine lung. In the air fryer drying kinetics, the samples obtained lower humidity in less than 20 min at a temperature of 160 ºC and around 100 min at 90 ºC. To this end, the results obtained in this work demonstrated that porcine lungs and hearts have the potential to be dried, making them interesting for different applications such as their incorporation into small animal feed. Keywords: Air Frying. Convective greenhouse. Freeze-drying. Drying. Meat by-product.